Antidepressant activity of Citrus limetta leaves in mice using battery of behavior models modulating via serotonergic systems - Jaspreet Kaur; Manisha Bhatia; Parminder Nain (Bangladesh Pharmacological Society, 2019)
The methanolic extract of Citrus limetta leaves was estimated in the present study for antidepressant activity. This activity was evaluated by using the rat behavioral model i.e. forced swimming and tail suspension model for 14 days, with estimation of neurotransmitters in animals brain. The sedative effect was evaluated by actophotometer. The extract (200 mg/kg) administered orally showed significant (p<0.05) decrease in immobility time against the standard drug fluoxetine (20 mg/kg, i.p), and imipramine (15 mg/kg, i.p.) respectively but no significant reduction was found in the locomotor activity against diazepam (2 mg/kg, i.p.). In depression, the brain reflected low monoamines level like release of norepinephrine, dopamine and serotonin but 14 days after successive administration of the extract, their levels were significantly increased. In conclusion, C. limetta showed significant antidepressant activity.   Video Clip of Methodology: Forced swimming test: 6 min 17 sec:  Full Screen   Alternate